Beneficial effect of steam on synthesis of hierarchically porous zeolite‐templated carbons. (23rd May 2022) - Han, Jinju; Kim, Kyoungsoo
Abstract: Hierarchically meso‐/microporous carbons were synthesized using nanocrystalline beta zeolite as a sacrificial template. The zeolite template possessed intercrystalline mesopores in addition to ordered micropores of the nanocrystals. Various amounts of steam were used with a carbon source, such as ethylene, propylene or acetonitrile, to generate a carbon structure inside the template. The synthesis results showed that adding a suitable amount of steam gave rise to faithful replication of the ordered microporous structure, while the intercrystalline mesopores were retained. That is, the carbon structure was formed selectively inside nanocrystalline zeolites rather than at the exterior by the steam addition. Microscopic observation and thermogravimetric analysis revealed that steam oxidized the carbon species deposited at the external surface of zeolite nanocrystals, and hence inhibited the undesirable carbon deposition. Furthermore, such a beneficial effect of steam could be applied for the carbon synthesis using other type zeolite templates. Abstract : In the carbon synthesis using nanocrystalline zeolite as a template, a suitable amount of steam mixed with carbon sources helps carbon deposition to occur selectively inside the zeolite micropores, and hence leads to obtain hierarchically porous carbon having both highly ordered microporous structure and interconnected mesoporosity.